2009
DOI: 10.1007/978-1-59745-196-3_14
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Insect Cell Protein Expression Applications

Abstract: The Baculovirus Expression Vector System (BEVS) is one of the most efficient systems for production of recombinant proteins and consequently its application is wide-spread in industry as well as in academia. Since the early 1970s, when the first stable insect cell lines were established and the infectivity of bacu-lovirus in an in vitro culture system was demonstrated (1, 2), virtually thousands of reports have been published on the successful expression of proteins using this system as well as on method impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Under these conditions cells can be grown to a density of $5 Â 10 6 cells/ml of culture, which is adequate for expression studies. Interestingly, it has been reported that P 1 viral titres obtained from amplification of viruses in suspension are usually 10-fold higher ($5 Â 10 8 pfu/ml) than for static cultures (Buchs et al, 2009), removing the need for further rounds of amplification to obtain a high titre viral stock. Although multiplicity of infection can be determined empirically by varying the volume ratio of P 1 virus to the number of cells infected, determining the precise titre of a baculovirus may sometimes be necessary, e.g., trouble-shooting lack of expression.…”
Section: Optimising Expressionmentioning
confidence: 99%
“…Under these conditions cells can be grown to a density of $5 Â 10 6 cells/ml of culture, which is adequate for expression studies. Interestingly, it has been reported that P 1 viral titres obtained from amplification of viruses in suspension are usually 10-fold higher ($5 Â 10 8 pfu/ml) than for static cultures (Buchs et al, 2009), removing the need for further rounds of amplification to obtain a high titre viral stock. Although multiplicity of infection can be determined empirically by varying the volume ratio of P 1 virus to the number of cells infected, determining the precise titre of a baculovirus may sometimes be necessary, e.g., trouble-shooting lack of expression.…”
Section: Optimising Expressionmentioning
confidence: 99%
“…Recently published high-throughput insect cell expression systems have streamlined expression screening and protein analysis, but still adhere to generating and amplifying recombinant baculoviruses for each individual construct (Mancia and Love, 2011;Hanson et al, 2007;Buchs et al, 2009). In Fig.…”
Section: Introductionmentioning
confidence: 99%
“…!,49]. System-based on the infection of insect cells with recombinant baculovirues often produce more proteins per litre, more economically, than mammalian cell expression systems.…”
Section: High-throughput Approaches For Eukaryotic Membrane Proteinsmentioning
confidence: 99%